The relationship between inflation and stock market: Evidence from Malaysia, United States and China - Caroline Geetha; Rosle Mohidin; Vivin Vincent Chandran Munusamy; Victoria Chong (OMICS Publishing, 2011)
The study aims to find the relationship between inflation and stock returns. Inflation was distinguished as expected and unexpected inflation. The study revealed that there is long run relationship between expected and unexpected inflation with stock returns but there is no short run relationship between these variables for Malaysia and US, but it exists for China.